Animals and anomalies: an analysis of the UK veterinary profession and the relative lack of state reform - Hobson-West, Pru; Timmons, Stephen (Wiley, 2016)
The sociology of professions literature would predict that the contemporary state would not allow groups to continue unregulated or unreformed. However, this is indeed the case with the UK veterinary profession, with legislation dating back to 1966. Using an interdisciplinary analysis of published literature and reports, this paper assesses whether wider social, political and ethical dynamics can better explain this intriguing anomaly. We conclude with critical implications for the sociology of the professions. Furthermore, we argue that continuing to ignore the veterinary profession, and animals more generally, in sociological research will result in an impoverished and partial understanding of contemporary healthcare and occupations.